Steviol, the aglycon of steviol glycosides, does not reduce hyperglycemia in mice with type 2 diabetes - Caroline Simoens; Caroline Wuyts; Ladan Khodaparast; Laleh Khodaparast; Séverine Goscinny; Els Van Hoeck; Joris Van Loco; Koenraad Philippaert; Bart Van der Schueren; Rudi Vennekens (Elsevier, 2022)
Background: Steviol glycosides, constituents of Stevia rebaudiana Bertoni, are high-intensity sweeteners that enhance glucose-induced insulin secretion and decrease hyperglycemia in mice and rats. Given the extreme sweetness and bitter aftertaste of these compounds, the non-tasting aglycon steviol might be a promising alternative food additive that also harbors anti-hyperglycemic effects. Furthermore, it has been suggested that steviol glucuronide is the main bioactive metabolite of steviol and steviol glycosides that appears in blood. Aim: To investigate whether steviol and/or steviol glucuronide reduce hyperglycemia in a high-fat diet (HFD)-induced diabetic mouse model. Methods: Steviol was administered acute per os (p.o.), chronic via drinking water and intravenous (i.v.) to HFD-induced diabetic mice. The effect on glucose homeostasis was assessed using glucose tolerance tests (GTTs). Following chronic and i.v. steviol administration, steviol and steviol glucuronide plasma levels were determined. Steviol glucuronide was administered i.v. and the effect on glycemia was assessed with GTTs. Results: Acute and chronic oral steviol administration did not lower glycemia. This is due to the very limited and short-lived bioavailability of steviol in plasma. Only after high dosage i.v. steviol, glycemia was transiently reduced shortly after administration (Δ 15 min: 76.4 ± 30.9 mg dL−1, p = 0.035). In contrast, i.v. steviol glucuronide resulted in a 16.4 ± 5.9% lower AUCGlucose(0-120 min) compared to mice that received vehicle (p = 0.040). Moreover, steviol glucuronide enhanced the glucose-induced calcium oscillation frequency in insulin-secreting pancreatic islets. Conclusion: Our findings demonstrate that steviol is not a useful derivative of steviol glycosides to improve hyperglycemia in type 2 diabetes. On the other hand, steviol glucuronide has significant anti-hyperglycemic effects in living mice with type 2 diabetes.